Structural insight into FANCI–FANCD2 monoubiquitination. Issue 5 (29th July 2020) - Li, Landing; Tan, Winnie; Deans, Andrew J.
Abstract: The Fanconi anemia (FA) pathway coordinates a faithful repair mechanism for DNA damage that blocks DNA replication, such as interstrand cross-links. A key step in the FA pathway is the conjugation of ubiquitin on to FANCD2 and FANCI, which is facilitated by a large E3 ubiquitin ligase complex called the FA core complex. Mutations in FANCD2, FANCI or FA core complex components cause the FA bone marrow failure syndrome. Despite the importance of these proteins to DNA repair and human disease, our molecular understanding of the FA pathway has been limited due to a deficit in structural studies. With the recent development in cryo-electron microscopy (EM), significant advances have been made in structural characterization of these proteins in the last 6 months. These structures, combined with new biochemical studies, now provide a more detailed understanding of how FANCD2 and FANCI are monoubiquitinated and how DNA repair may occur. In this review, we summarize these recent advances in the structural and molecular understanding of these key components in the FA pathway, compare the activation steps of FANCD2 and FANCI monoubiquitination and suggest molecular steps that are likely to be involved in regulating its activity.